2011
DOI: 10.1364/ome.1.001100
|View full text |Cite
|
Sign up to set email alerts
|

Colored semi-transparent Cu-Si oxide thin films prepared by magnetron sputtering

Abstract: Colored semi-transparent Cu-Si oxide thin films have been prepared by reactive magnetron sputtering from a single cathode of coppersilicon composition. Thin films of different composition and optical response were obtained by changing process parameters like the relative amount of copper in the target and the O 2 /Ar mixture of the reactive plasma gas. The film characteristics were analyzed by several techniques. Their optical properties (refractive index, absorption coefficient, color) have been correlated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 28 publications
3
15
0
Order By: Relevance
“…13 multi-component oxide coatings deposited at room temperature has also been reported by GilRostra et al for a variety of mixed-valent films [15,[17][18][19].…”
Section: Accepted Manuscriptsupporting
confidence: 55%
See 2 more Smart Citations
“…13 multi-component oxide coatings deposited at room temperature has also been reported by GilRostra et al for a variety of mixed-valent films [15,[17][18][19].…”
Section: Accepted Manuscriptsupporting
confidence: 55%
“…While most of these applications require fully stoichiometric, transparent oxide mixtures, recent works exploring sub-stoichiometric oxide systems have generated interest due to their unique absorptive properties [15][16][17]. Specifically, studies by GilRostra et al [15,[17][18][19] have utilized reactive magnetron sputtering to tailor the visible absorption of substoichiometric transition metal oxides, including Ni [15], Co [15,19], Fe [15], Cu [15,18], W [15,17], and Mo [15], within a dielectric silicon dioxide matrix. Gil-Rostra et al…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar interpretation has been adopted for the other series of mixed oxide thin film samples [17,19,22,23]. The initial VF for pure SiO 2 is about 15% [18].…”
Section: / 26mentioning
confidence: 58%
“…It was found that the film stoichiometry depends on the number of metal stripes wrapped to the Si target. The correlation between metal stripes in the target and thin film stoichiometry has been reported elsewhere [17,19]. [14][15][16].…”
Section: Thin Film Compositionmentioning
confidence: 99%